Synergistic efficacy of insecticides and phytochemicals against rugose spiraling whitefly (Aleurodicus rugioperculatus) in India - Sudesna , R; Sashanka , S D; Manoj , K T; Manas , R K; Prasanjit , M (Plant Science Today, 2025)
The rugose spiraling whitefly (Aleurodicus rugioperculatus Martin), an invasive pest impacting coconut and banana crops in India, exhibits adaptability and resistance to conventional insecticides, posing significant agricultural challenges. This study assessed the efficacy of imidacloprid, spiromesifen and thiodicarb, alone and combined with synergists (piperonyl butoxide, PBO, diethyl malate, DEM, propargyloxy phthalimide, PP) and plant extracts, against RSW populations from Bhubaneswar, India, in 2024. Leaf dip bioassays determined LC₅₀ values, synergistic ratios (SRs) and 24 hr mortality rates. Spiromesifen demonstrated the highest efficacy (LC₅₀ 0.431 ppm in January), followed by imidacloprid (0.458 ppm) and thiodicarb (0.528 ppm). Synergism with PBO markedly enhanced potency, reducing spiromesifen’s LC₅₀ to 0.046 ppm (SR 9.956), imidacloprids’ to 0.108 ppm (SR 3.990) and thiodicarb’s to 0.140 ppm (SR 3.771). Plant extract combinations yielded up to 75 % mortality with spiromesifen and Pongamia oil, 70 % with thiodicarb and Pongamia oil and 60 % with imidacloprid and sesamum oil. Seasonal resistance increased LC₅₀ values by 34-64 % from January to May (e.g., thiodicarb 0.865 ppm), reflecting heightened resistance in warmer conditions. These results highlight that integrating synergists and phytochemicals with insecticides significantly boosts rugose spiraling whitefly (RSW) control, reducing required doses by up to 92 % and mitigating resistance. This approach offers a sustainable pest management strategy for Indian agriculture, particularly in coastal regions where RSW thrives. Field trials are recommended to validate these laboratory findings and refine integrated pest management practices.